1998
DOI: 10.1073/pnas.95.2.669
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a high-affinity stable single-chain Fv specific for mesothelin from DNA-immunized mice by phage display and construction of a recombinant immunotoxin with anti-tumor activity

Abstract: Mesothelin is a differentiation antigen present on the surface of ovarian cancers, mesotheliomas, and several other types of human cancers. Because among normal tissues, mesothelin is present only on mesothelial cells, it represents a good target for antibody-mediated delivery of cytotoxic agents. In the present study mice were immunized with an eukaryotic expression vector coding for mesothelin. When high serum antibody titers were obtained, a phage display library was made from the splenic mRNA of these mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
133
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(139 citation statements)
references
References 25 publications
3
133
1
Order By: Relevance
“…The mouse-human chimeric IgG1k monoclonal antibody amatuximab has a binding affinity of 1.5 nM for human mesothelin (137). Two phase I clinical trials identified a maximum tolerated dose of 200 mg/m 2 ; however, no responses were seen in patients with MPM who received this agent (138,139).…”
Section: Amatuximabmentioning
confidence: 99%
“…The mouse-human chimeric IgG1k monoclonal antibody amatuximab has a binding affinity of 1.5 nM for human mesothelin (137). Two phase I clinical trials identified a maximum tolerated dose of 200 mg/m 2 ; however, no responses were seen in patients with MPM who received this agent (138,139).…”
Section: Amatuximabmentioning
confidence: 99%
“…In contrast with published antimesothelin antibodies (10,(32)(33)(34)(35), our mouse monoclonals were raised to unfolded, nonglycosylated mesothelin extracellular domain (with and without MPF). Hybridoma supernatants were screened by ELISA, followed by FACS and IHC analysis of cells stably transfected with mesothelin to select those capable of detecting native glycosylated and formalin-fixed mature mesothelin, respectively (data not shown).…”
Section: Antibody Linker and Drug Selectionmentioning
confidence: 99%
“…The primary outcome is progression free survival (Clinicaltrials.gov identifier: NCT 00738582). SS1P is a recombinant immunotoxin made up of an antimesothelin Fv fragment linked to a truncated Pseudomonas exotoxin (Chowdhury and Viner, 1998). A single center, phase I clinical trial evaluating dose escalation of SS1P with concurrent administration of cisplatin and pemetrexed in unresectable epithelioid MPM patients is underway (Clinicaltrials.gov identifier: NCT01445392).…”
Section: Experimental Therapy Of Malignant Mesotheliomamentioning
confidence: 99%